Longitudinal Study of Pelvic Floor Characteristics Before, During, and After Pregnancy in Nulliparous Women. (7th March 2021) - Lakovschek, Ioana‐Claudia; Trutnovsky, Gerda; Obermayer‐Pietsch, Barbara; Gold, Daniela
Abstract : Objectives: To investigate the changes in the pelvic floor before, during, and after pregnancy in the same collective of nulliparous women. Methods: In a prospective observational pilot study between April 2015 and June 2019 in nulliparous women with planned pregnancy, we used the pelvic organ prolapse quantification (POP‐Q) system; a 2‐dimensional (2D) sonography to investigate the bladder neck, cervix, and anorectal junction positions; and a 3D/4D sonography to measure the hiatus of the levator ani muscle (LH area) during Valsalva maneuver. Five visits were planned: 1 before, 3 during, and 1 visit after pregnancy. Results: Twenty‐four women participated in the study. We achieved a minimum of 2 visit measurements from 10 women who became pregnant. The LH area decreased during the first trimester and then increased until the third trimester. Postpartum, the LH area reached the prepregnancy state. We observed changes in the bladder neck mobility, bladder neck position, cervix, and anorectal junction from the first trimester. Postpartum, the bladder neck mobility was higher, and the position of the bladder neck and anorectal junction was lower than before pregnancy. We observed no remarkable changes in the POP‐Q state during pregnancy. Conclusion: This was the first study to investigate pelvic floor characteristics in the same collective before, during, and after pregnancy. We observed pelvic floor changes from the prepregnancy state to the first trimester to postpartum. The study results need to be confirmed in a larger study. Abstract : Access the CME test here and search by article title.